Understanding of School Related Factors Associated with Emotional Health and Bullying Behavior among Jordanian Adolescents. - Abeer Shaheen; Omayyah Nassar; Mohammad Saleh; Diana Arabia T (Tehran University of Medical Sciences, 2014)
Students emotional health and bullying behavior are receiving greater attention worldwide due to their long-term effects on students' health. The purpose of this study was to examine the relationships between perceived school climate, peer support, teacher support, school pressure and emotional health and bullying among adolescent school students in Jordan.A cross-sectional descriptive design was used to recruit a sample of 1166 in-school adolescents in Amman between November 2013 and January 2014. A multi-stage cluster sampling technique was used to select respondents and Health Behavior in School Aged Children questionnaire was used to collect the data. Data were analyzed using Pearson Correlation to detect relationships among study variables.Significant correlations (P value was ≤.05) were found between school climate including teacher and peer support and emotional health and bullying behavior of school students. School pressure was not correlated significantly with emotional health and bullying.Study findings emphasize the importance of school related factors in influencing students' emotional health and bullying behavior. This indicates that the issue of bullying and emotional health of students in Jordanian schools requires further attention, both for future research and preventive intervention.